Associative Factors Involved in Avoidance of Exclusive and Non-Exclusive Breastfeeding after C-section - Asbah Rahman; Qudrat Ullah Malik; Muhammad Faisal Shafiq; Shaista Mumtaz; Muhammad Waleed Babar; Saira Akram (Pakistan Armed Forces Medical Journal, 2022)
Objective: To look for the associative factors in avoidance of exclusive and non-exclusive breastfeeding among mothers after lower segment Caesarean section.